to know the impact of intensity of competition on some physical and physiological elements A field study for( uss) oum boughi - Messaoudi, abdrahman; ghadban, hamza (sports creativity, 2025)
The aim of the study was to know the impact of intensity of competition on some physical and physiological elements, and this after applying the program to follow the time of each player’s participation in all friendly matches, which amounted to 6 interviews and the with a total time of and half months on A group of major football players numbering 24, a set of physical and physiological tests were applied and the statistical treatment using spss.